Efeito e segurança de 6,7-dimetoxi-3-nitrocumarina (composto semissintético modificado a partir da 6,7-dimetoxicumarina obtida do caule de platymiscium floribundum vog) em um modelo de periodontite em ratas - França, Ana Larissa de Queiroz (2020)
Periodontitis is an inflammation of the supporting tissues of the teeth with progressive loss of insertion and bone destruction as a result of the host's response to the presence of a dysbiotic microbiota. Thus, this study aimed to evaluate the anti-resorptive activity and safety of 6,7-dimethoxy-3-nitrocoumarin, modified from 6,7-dimethoxycoumarin obtained from the stem of Platymiscium floribundum in ligature-induced periodontitis in rats and the involvement of the HO-1 pathway in its mechanism of action. Periodontitis was induced by placing a sterile nylon (3.0) ligature around the left upper second molars. The rats received (oral gavage) once a day, for 11 days, 6,7-dimethoxy-3-nitrocoumarine (0.01, 0.1 or 1 mg / kg) or vehicle (0.9% saline solution + ethanol 0.1%). 6,7-dimethoxy-3-nitrocoumarin (0.1 or 1 mg / kg) reduced alveolar bone loss (1.88 ± 0.15; 1.05 ± 0.24, respectively), when compared to the group treated with vehicle (3.05 ± 0.30). 6,7-dimethoxy-3-nitrocoumarin (1 mg / kg) reduced levels of TNF-ɑ (2.33 ± 0.56) and IL-1β (19.87 ± 2.9) mRNA, while increasing HO-1 mRNA levels (43.40 ± 1.05) and catalase activity (46.42 ± 4.59), when compared to the vehicle-treated group (46.29 ± 8.43; 37.83 ± 4.38; 1.58 ± 0.11; 8.93 ± 1.86, respectively). There were no statistical differences (P> 0.05) in serum biochemical parameters (creatinine, TALP, ALT, AST) between groups. 6,7-dimethoxy-3-nitrocoumarin decreased inflammatory bone loss in ligature-induced periodontitis in rats and activation of the HO-1 pathway contributes at least partially to its protective effects